Application Of Chat Bot For Student's Counseling Guidance At SMK Negeri 1 Bengkulu City - Alexsander, Alexsander; Aspriyono, Hari; Beti, Ilayati (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2025)
SMK Negeri 1 Bengkulu City is a vocational high school located in Bengkulu City. Guidance and counseling services at school to help students in an effort to find themselves, get to know the environment and plan for the future of students. The purpose of this research is to facilitate students in obtaining counseling guidance information, conducting counseling guidance, and also reporting a finding of events that occur at school. Chat Bot Application of Students’ Counseling Guidance at SMK Negeri 1 Bengkulu City can be accessed online, where there are 2 interfaces, namely web-based which is accessed through the link https://bkchatbotsmkn1bkl.site/ and chat bot-based which can be accessed via telegram with @chatbotkonseling bot account. Chat Bot Application for students’ counseling guidance at SMK Negeri 1 Bengkulu City can facilitate and assist students in conducting students’ counseling through chat bot application, so that the problems experienced are known. In addition, this application can facilitate students in obtaining counseling guidance information, conducting counseling guidance, and also reporting a finding of events that occur in school environment at SMK Negeri 1 Bengkulu City. Based on counseling conducted through telegram chatbots on students, the results show that the system can reply to messages automatically according to the message command format sent by students via telegram, and the system can help provide information on the results of counseling according to the knowledge based on symptoms felt by students through the command format that has been set in the system and successfully display the results of counseling guidance. Based on the results of the alpha testing, it can be concluded that this telegram chat bot application is quite helpful in students’ counseling guidance and will be used by SMK Negeri 1 Bengkulu City.